MODEL BISNIS CV. COREN LOMBOK DENGAN PENDEKATAN BUSINESS MODEL CANVAS (BMC) - Putri Ayu Pupuh; I.A.Y.S.D Utami Pidada; Muh. IIham H (Juremi: Jurnal Riset Ekonomi, 2024)
The Business Model Canvas is one of the managerial tools used to analyze a business model within the company which can also be used to evaluate the business model if there are changes that occur both internally and externally. This research was conducted to find out the business model currently being run by the CV. Coren Lombok company using primary data types with observation, documentation, and interview methods. This research is adescriptive qualitative research with an analysis method of 9 building blocks of the Canvas Business Model. The result is that CV. Coren Lombok has implemented its business model with the guidelines of the 9-block Business Model Canvas even though it does not yet have a physical form of the managerial tool